CONVENTION REPORT. (The Accounting Review, 1935)
Abstract The nineteenth annual convention of the American Association of University Instructors in Accounting was held in the Palmer House, Chicago, Illinois on December 27 and 28, 1934. On December 27, the topic of the convention was "Methods of Teaching Accounting." Several speakers from different universities of the United States read papers. On December 28, the topic of the convention was, "Accounting Relationships." Professor H.F. Taggart from the University of Michigan, professor J.B. Heckert, from Ohio State University, etc, read papers related to various issues on accounting. The annual meeting of the Executive Committee was held on December 27. The committee first heard a brief preliminary report of finances by the Secretary-Treasurer. E.J. Filbey, H.H. Bailey, and G. E. Lukas, all certified public accountants of Illinois, were appointed as auditors of the Secretary-Treasurer's books for the year. The committee ordered that the report of the auditors be published in the March 1985 issue of the journal The Accounting Review.